2018
DOI: 10.3171/2017.12.focus17670
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cochlear implantation as a therapeutic option in vestibular schwannoma surgery: case report

Abstract: Hearing loss is the most common symptom of vestibular schwannomas (VSs). The management of these lesions includes observation, radiosurgery, and microsurgical resection. Hearing preservation and rehabilitation are the major challenges after the tumor treatment. A 43-year-old man with previous left-sided profound hearing loss and tinnitus presented with a 2-mm left-sided intracanalicular VS. The decision was made to perform a simultaneous cochlear implantation (CI) and microsurgical resection of the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Cochlear implantation is a relatively new indication for hearing restoration in some VS patients and is relevant when the cochlear nerve is preserved during microsurgical tumor resection, following stereotactic radiation surgery, or when tumor resection is not attempted due to the tumor’s small size and the patient’s overall medical condition [ 84 ]. A retrospective cohort study of VS patients with tinnitus reported that median Tinnitus Handicap Inventory scores significantly improved after CI implantation (n = 17) [ 80 ], which is consistent with several prior small cohort studies that also reported improvements in tinnitus symptoms with CIs [ 85 , 86 , 87 ]. However, VS tumor management and the tumors themselves may have unpredictable effects on CIs’ function given the damage to the vestibulocochlear nerve.…”
Section: Discussionsupporting
confidence: 85%
“…Cochlear implantation is a relatively new indication for hearing restoration in some VS patients and is relevant when the cochlear nerve is preserved during microsurgical tumor resection, following stereotactic radiation surgery, or when tumor resection is not attempted due to the tumor’s small size and the patient’s overall medical condition [ 84 ]. A retrospective cohort study of VS patients with tinnitus reported that median Tinnitus Handicap Inventory scores significantly improved after CI implantation (n = 17) [ 80 ], which is consistent with several prior small cohort studies that also reported improvements in tinnitus symptoms with CIs [ 85 , 86 , 87 ]. However, VS tumor management and the tumors themselves may have unpredictable effects on CIs’ function given the damage to the vestibulocochlear nerve.…”
Section: Discussionsupporting
confidence: 85%
“…13,14 There were 5 of the 21 subjects who either did not have open-set recognition tested or were not reported. [18][19][20][21] One of these subjects had subjective recognition, but formal testing was deferred due to the patient only speaking Spanish. 19 A subject detailed by dos Santos Neto et al showed improvement in both Ling Sound Test and identification of vocabulary extension compared to baseline measures.…”
Section: Speech Perception Outcomesmentioning
confidence: 99%
“…19 A subject detailed by dos Santos Neto et al showed improvement in both Ling Sound Test and identification of vocabulary extension compared to baseline measures. 21…”
Section: Speech Perception Outcomesmentioning
confidence: 99%
“…For the patients with TFIAC grade III or TFIAC grade IV, cochlear implantation may provide a favorable hearing restoration, which will apparently reopen discussions about AN management. Some studies have suggested surgical tumor removal combined with cochlear implantation is a promising treatment strategy in the management of AN patients with unilateral hearing loss and severe tinnitus [42,43]. In our study, we found that TFIAC grade III or IV AN patients had lower rates of hearing preservation after surgical treatment, suggesting that these patients had limited hearing preservation benefits from tumor removal.…”
Section: Tfiac Classification Determines the Optimal Timing Of Interventionmentioning
confidence: 44%